Structure and reactivity of ZSM-5 supported oxalate ligand functionalized nano-Fe catalyst for low temperature direct methane conversion to methanol - Ayodele, O.B. (Elsevier Ltd, 2016)
The feasibility of low temperature direct methane conversion to methanol (DMCM) over ferrioxalate supported on ZSM-5 catalyst (FeOx/ZSM-5) was investigated in this study. FeOx/ZSM-5 was synthesized via functionalization of Fe with oxalate ligand and employed to generate hydroxyl radicals (HO) from hydrogen peroxide (HP) in a Fenton-like process to activate the methane Formula presented bond scission to form methoxyl radical which in turn reacted with water to form methanol. The Fourier transformed infrared (FTIR) spectroscopy result showed the presence of Î½a(Formula presented) from the oxalate anion (C2O42â) at 1655 cmâ1 and Î½3 asymmetry stretch from CO32â at 1343 cmâ1. The presence of Fe in the catalyst was elucidated by the energy dispersive X-ray, X-ray diffraction patterns and X-ray photoelectron spectroscopy (XPS). Furthermore, the XPS results showed that Fe2+/Fe3+ ratio in FeOx/ZSM-5 was 4.29. The effect of operating conditions showed that while FeOx/ZSM-5 loading and reaction time followed a simple power function (y = a Â· xn), the effect of HP dosage followed exponential function (y = a Â· ex), which signifies that the latter is more significant. The used-FeOx/ZSM-5 characterization result showed that virtually all the Fe2+ have been oxidized to Fe3+ after 15 min of reaction time. This novel result is promising for further research towards commercial low temperature DMCM. Â© 2016 Elsevier Ltd